2002
DOI: 10.1128/iai.70.4.1881-1888.2002
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine and Exocrine Regulation of Interleukin-10 Production in THP-1 Cells Stimulated withBorrelia burgdorferiLipoproteins

Abstract: We have recently demonstrated that interleukin-10 (IL-10), produced by THP-1 monocytes in response to Borrelia burgdorferi lipoproteins, dampens the production of concomitantly elicited inflammatory cytokines. Thus, IL-10 could potentially down-regulate inflammatory and microbicidal effector mechanisms of the innate immune response to a B. burgdorferi infection, facilitating the establishment of the spirochete. To understand the mechanism(s) implicated in the regulation of the synthesis and release of IL-10 du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 49 publications
7
38
0
1
Order By: Relevance
“…In addition, we have demonstrated that bacterial lipoproteins also can elicit the production of IL-10, an anti-inflammatory cytokine, in both human and monkey monocytes (29). Both autocrine and exocrine inhibition of IL-10 production resulted in an increase in the production of the proinflammatory cytokines IL-6 and IL-12 (30). The findings that lipoproteins can elicit not only inflammatory, but also anti-inflammatory mediators, e.g., IL-10 from monocytes, have added support to the contention that lipoproteins are crucial factors in the pathogenesis of bacterial infections.…”
mentioning
confidence: 51%
“…In addition, we have demonstrated that bacterial lipoproteins also can elicit the production of IL-10, an anti-inflammatory cytokine, in both human and monkey monocytes (29). Both autocrine and exocrine inhibition of IL-10 production resulted in an increase in the production of the proinflammatory cytokines IL-6 and IL-12 (30). The findings that lipoproteins can elicit not only inflammatory, but also anti-inflammatory mediators, e.g., IL-10 from monocytes, have added support to the contention that lipoproteins are crucial factors in the pathogenesis of bacterial infections.…”
mentioning
confidence: 51%
“…In mice, cultured monocytes from C3H/HeJ mice, which are more susceptible to Lyme arthritis, produced lower amounts of IL-10 than monocytes from the more resistant strain C57BL/6J. 33 Furthermore, IL-10 deficiency in C57BL/6J mice resulted in more severe arthritis. 28 It is possible that reduced IL-10 production by C3H/HeJ mice explains their increased susceptibility to arthritis during B. burgdorferi infection.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous TNF-␣ has been reported to augment IL-10 production in monocytes [40], and IL-10 has also been demonstrated to suppress LPS-induced IL-6 and IL-12 production [41]. We considered the possibility that enhanced production of TNF-␣ by p110␣-deficient cells might have led to augmented IL-10 production through a paracrine effect and that this may have led to suppression of IL-6 and IL-12.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous TNF-␣ has been reported to augment IL-10 production by monocytes [40]. We considered the possibility that enhanced TNF-␣ production by p110␣-deficient cells might bring about augmented IL-10 production via a paracrine effect.…”
Section: Lps-induced Cytokine Production In Thp-1 Cells Is Mediated Tmentioning
confidence: 99%